Modularity of the Mtr respiratory pathway of Shewanella oneidensis strain MR-1 - Coursolle, Dan; Gralnick, Jeffrey A (Molecular microbiology, 2010)
Four distinct pathways predicted to facilitate electron flow for respiration of externally located substrates are encoded in the genome of Shewanella oneidensis strain MR-1. Although the pathways share a suite of similar proteins, the activity of only two of these pathways has been described. Respiration of extracellular substrates requires a mechanism to facilitate electron transfer from the quinone pool in the cytoplasmic membrane to terminal reductase enzymes located on the outer leaflet of the outer membrane. The four pathways share MtrA paralogues, a periplasmic electron carrier cytochrome, and terminal reductases similar to MtrC for reduction of metals, flavins and electrodes or to DmsAB for reduction of dimethyl sulphoxide (DMSO). The promiscuity of respiratory electron transfer reactions catalysed by these pathways has made studying strains lacking single proteins difficult. Here, we present a comprehensive analysis of MtrA and MtrC paralogues in S. oneidensis to define the roles of these proteins in respiration of insoluble iron oxide, soluble iron citrate, flavins and DMSO. We present evidence that some periplasmic electron carrier components and terminal reductases in these pathways can provide partial compensation in the absence of the primary component, a phenomenon described as modularity, and discuss biochemical and evolutionary implications.